Peran Kepala Sekolah dalam Melaksanakan Fungsi Manajerial untuk Meningkatkan Mutu Sekolah di SMP Islam YPI 3 Way Jepa - Essa Affrilian (Penerbit Goodwood, 2023)
Purpose: This study is to determine the role of school principals in carrying out managerial functions to improve school quality. Method: This research is descriptive qualitative research. The implementation managerial functions is based on the stages in the management process, namely planning, organizing, implementing and supervising. Result: Having a good school quality, namely by creating a school program that is carried out in collaboration with all school members, has implemented a school program plan starting from planning the learning process, implementing, providing assessments and supervising learning.